2020
DOI: 10.3390/cancers12092595
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Breast and Endometrial Cancers

Abstract: Cancers of the breast and endometrium are some of the most common cancers affecting women [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wang et al demonstrated the superiority of the prognostic accuracy of multiRNA combined with clinical-stage over clinical stage alone, according to FIGO and over some genetic prognostic predictive models available in the literature [95]. Some recent reviews had already highlighted the role of ncRNAs in developing female cancers [8,98,99], but they mainly focused on their mechanism in tumorigenesis. The present review is the first to identify and select a pool of ncRNAs that have a prognostic role and can influence the therapeutic choice based on the epigenetic profile of EC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated the superiority of the prognostic accuracy of multiRNA combined with clinical-stage over clinical stage alone, according to FIGO and over some genetic prognostic predictive models available in the literature [95]. Some recent reviews had already highlighted the role of ncRNAs in developing female cancers [8,98,99], but they mainly focused on their mechanism in tumorigenesis. The present review is the first to identify and select a pool of ncRNAs that have a prognostic role and can influence the therapeutic choice based on the epigenetic profile of EC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hormones, especially steroids, are closely involved in the physiological functions and proliferation of various target tissues and have long been known to play a key role in the tumorigenesis or carcinogenesis of these target tissues. It is well known that sex steroid hormones, such as estrogen and androgen, have a close influence on the development and malignant behavior of endometrial, ovarian, and breast cancers in women and prostate cancer in men [ 1 , 2 ]. These cancers are hormone-dependent, and some of the mechanisms of hormone action have been identified as therapeutic targets.…”
mentioning
confidence: 99%
“…Therefore, research on the crosstalk between the ER and receptors for physiologically active substances, including hormones, is required to further elucidate ER signaling in breast cancer cells. Cancer tissue is composed of parenchymal cancer cells and surrounding stromal cells; the intratumoral stroma includes fibroblasts, adipocytes, inflammatory cells, and capillaries [ 1 ]. Adipose stem cells (ASCs) from obese donors secrete abundant leptin and increase ERα and aromatase expression in breast cancer [ 11 ].…”
mentioning
confidence: 99%